Community-level expenses for under-5 diarrhoeal cases prior to reporting at Dhaka Hospital: A cross-sectional analysis in Bangladesh - Md Fuad Al Fidah; Md Ridwan Islam; Md Mushfiqur Rahman; Mohammod Jobayer Chisti; A.S.G. Faruque; Tahmeed Ahmed; Sharika Nuzhat (Clinical Epidemiology and Global Health)
Background: Diarrhoeal diseases are a major public health challenge, placing immense economic burden on households. We aimed to examine the trends in direct medical costs (DMC), direct non-medical costs (DNMC), and family economic burden (FEB) incurred in the community before seeking care at the Dhaka Hospital. Methods: DMC and DNMC were extracted from the database of the DDSS of Dhaka Hospital of the International Centre for Diarrhoeal Disease Research, Bangladesh (icddr,b) from 2012 to 2021. Costs in the community were calculated after adjusting for inflation and converting into international dollars (I$) for 2022. The Jonckheere-Terpstra test examined the trends, and quintile regression was used. Results: The sample size was 14178. The median (IQR) direct cost, DMC, DNMC and FEB were I$26.2(14.5–44.9), I$10.1(3.6–21.3), I$13.11(7.5–22.3) and 3.5 %(1.8–6.9 %) respectively. An overall increasing trend (2.9 % in 2012 to 4.3 % in 2021; p-value<0.001) and a recent declining trend (from 4.6 % in 2020) were seen in FEB. Age, distance from home, time taken to reach the hospital, living inside Dhaka, wealth index, and moderate-to-severe disease were associated with all costs. Adequate maternal media exposure (coef: 0.698; 95%CI: 1.167 to −0.229; p-value = 0.004) and secondary level education of the mother (coef: 0.316; 95 % CI:0.018 to 0.614; p-value = 0.038) were negatively associated, COVID-19 period was positively associated (coef:0.786; 95 % CI:0.591 to 0.981; p-value<0.001) with FEB. Conclusion: FEB showed significant trend from 2012 to 2021. The result indicates the need for increased awareness and health education on using immediate oral rehydration therapy and seeking care directly from facilities when institutional care is needed.